Analisis Tingkat Kecelakaan Kerja dengan Metode AHP Pada Perumahan Royal Bazar dan Perumahan Royal Nyalaran di Kabupaten Pamekasan - Syaifuddin; Zabadi, Fairus (SLUMP TeS : Jurnal Teknik Sipil, 2024)
One of the factors that can hinder the achievement of the targets of a construction project is work accidents. According to BPJS Employment statistical data, the number of work accidents in 2019 reached 129,111 cases. Most of the work accidents or about 69.59% occurred inside the company while working, while 10.26% occurred outside the company and 20.15% were traffic accidents experienced by workers.. The object to be discussed is the level of work accidents in residential construction projects. From this object, the level of work accidents in housing construction projects will be analyzed using the Analytic Hierarchy Process (AHP) method and assisted with supporting applications, namely Expert Choice. The population used in this study are all parties involved in each housing construction project, such as contractors, planning consultants, workers, and developers of each housing construction project. Based on the data obtained, it is known that there are 3 contractors, 3 planning consultants, 43 workers and 6 developers from each housing project.